Mathematical modelling and bifurcation analysis of an eco-epidemiological system with multiple functional responses subjected to Allee effect and competition - Samim Akhtar; Nurul Huda Gazi; Sahabuddin Sarwardi (Results in Control and Optimization, 2024)
This article deals with an eco-epidemiological predator–prey model system with Allee effect on prey species and different functional responses. The growth function of the prey species is considered to follow Allee effect as this effect has an important and fundamental aspect on population growth. In this study we explore stability behaviour of the system along with bifurcation properties. It is also shown that the system experiences chaotic behaviour via period-doubling bifurcation as the parameters pass through some threshold values. The study’s validity is authenticated through numerical simulations using appropriate tools. The numerical simulations reveal that the system exhibits diverse dynamic behaviours with slight variations in system parameters.